The association between tidal volume and neurological outcome following in-hospital cardiac arrest. (March 2018) - Moskowitz, Ari; Grossestreuer, Anne V.; Berg, Katherine M.; Patel, Parth V.; Ganley, Sarah; Casasola Medrano, Marcel; Cocchi, Michael N.; Donnino, Michael W.
Abstract: Aims: Prior investigation has found that mechanical ventilation with lower tidal volumes (Vt) following out-of-hospital cardiac arrest is associated with better neurologic outcomes. The relationship between Vt and neurologic outcome following in-hospital cardiac arrest (IHCA) has not previously been explored. In the present study, we investigate the association between Vt and neurologic outcome following IHCA. Methods: This was an observational study using a prospectively collected database of IHCA patients at a tertiary care hospital in the United States. The relationship between time-weighted average Vt per predicted body weight (PBW) over the first 6- and 48 h after cardiac arrest and neurologic outcome were assessed using propensity-score adjusted logistic regression. Measurements and main results: Of 185 IHCA patients who received invasive mechanical ventilation within 6 h of return of spontaneous circulation (ROSC), the average Vt over the first 6 h was 7.7 ± 2.0 ml/kg and 68 (36.8%) patients received an average Vt > 8.0 ml/kg. Of 121 patients who received mechanical ventilation for at least 48 h post-ROSC, the average Vt was 7.6 ± 1.5 ml/kg and 46 (38.0%) patients received an average Vt > 8.0 ml/kg. There was no relationship between Vt/PBW over the first 6- or 48 h post-ROSC and neurologic outcome (OR 0.99; 95%CI 0.84–1.16; p = 0.89; OR 1.03; 95%CI 0.78–1.37; p = 0.83 respectively). Conclusions: This study did not identify a relationship between Vt and neurologic outcome following IHCA. This contrasts with results in OHCA, where higher Vt has been associated with worse neurologic outcome. Additional investigation is needed with respect to other potential benefits of low-Vt post IHCA.